Beyond Harmonization Exploring the Synergies of ACGS Implementation in Singapore, Thailand and Indonesia - Rahmawati, Apriana; Faruqi Febri Yanto, Alif; Prasetya, Rizky (Dinasti Publisher, 2024)
This study analyzes the ASEAN Corporate Governance Scorecard (ACGS) performance of three companies: Keppel (Singapore), Central Retail (Thailand) and Bakrie & Brothers (Indonesia). This research employs a qualitative method with a descriptive approach. The data analysis technique used is document content analysis. The data analysis procedure is carried out by collecting data sources, analyzing the collected data using the ASEAN Corporate Governance Scorecard and calculating the final score based on the predetermined weights. The results of this study indicate that Central Retail achieved the highest score among the companies, followed by Keppel and Bakrie, in the implementation of ASEAN Corporate Governance Scorecard Level 1. This finding aligns with institutional theory, which suggests that the implementation of corporate governance (CG) practices is influenced by institutional norms and expectations, as reflected in the ASEAN Corporate Governance Scorecard.